Archive Management at the Citta Sub-District Office Soppeng Regency - Lukman, Alfiah; Nasrullah, Muh.; Jamaluddin, Jamaluddin (Pinisi Journal of Officers Review, 2025)
Archive manaegement is a process for organizing, managing, and maintaining important archives or documents. This study aims to determine the effectiveness of archive manaegement at the Citta sub-district office. This research approach is a qualitative research approach and a type of descriptive research. The data collection techniques carried out in this study are using observation, interview, and documentation methods. The data analysis techniques used are data condensation, data presentation, and conclusion drawn. The results of this study show that all indicators used in the archive manaegement research at the Citta Sub-district Office are classified as less effective. This is evidenced by the indicator of archive creation that is classified as less effective because there are several disposition sheets that are allowed to accumulate so that the disposition sheets are scattered. Indicators of the use and maintenance of archives are classified as less effective because the archives that have been created are not properly maintained due to the lack of archival storage facilities provided, such as the absence of an ordner folder. The archive shrinkage indicator is classified as less effective because employees are less attentive in carrying out the archive shrinkage process so that the retention period in archives is neglected. This study presents new information by linking detailed theories and research loci that are different from previous research on archive manaegement so that it can be used as evaluation material for research loci to improve the quality of archive manaegement.